Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas Perusahaan Ritel Indonesia: Peran Moderasi Makroekonomi - Rezki Erdian; Hermanto Siregar; Dikky Indrawan (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Working capital management has an important role on firm profitability especially for retail firms operating in emerging countries. Previous studies have not really considered the influence of macroeconomic conditions on working capital management and firm profitability relation. This paper investigates the impact of working capital management on firm profitability among Indonesian retail firms listed on Indonesia Stock Exchange with the moderation of GDP growth (GDP) and working capital loan interest rate (IR). This study uses panel data regression covering the period of Q1 2016 – Q2 2021. The results show that days inventory outstanding (DIO) has negative impact on gross operating profit (GOP) and return on asset (RoA) while days payable outstanding (DPO) has positive impact on RoA and cash cycle (CCC) has positive impact on gross operating profit (GOP). The results also show that GDP moderates the relationship between CCC components and GOP, while IR moderates the relationship between DIO and both firm profitability indicators, DPO and RoA, CCC and GOP. The results suggest retail firm management to pay attention to its inventories, payables and cash cycle. The management also has to consider the GDP growth and interest rate in managing its working capital. Keywords: macroeconomy, working capital management, profitability, data panel regression, retail